Work Motivation and Its Impact on Employee Satisfaction and Performance in Islamic Boarding Schools - Wijaya, Nauval Fadhillah Gusti; Widiastuti, Tika (Universitas Airlangga, 2025)
This study aims to examine the impact of work motivation on employee satisfaction and performance at Al-Qur’an Nurul Falah Islamic Boarding School located in East Java. In addition, the study explores the role of employee satisfaction as a mediating variable in the relationship between work motivation and employee performance. The research employs a quantitative approach, utilizing data analysis techniques through Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through a survey using questionnaires distributed to employees within the boarding school environment. To evaluate the research model, tests were conducted to assess validity and reliability using convergent validity, discriminant validity, composite reliability, as well as path coefficient analysis to determine the relationships between variables. The results indicate that work motivation has a significant and positive influence on employee satisfaction, with a T-statistic value of 4.636 (p < 0.05). Furthermore, employee satisfaction significantly and positively affects performance, with a T-statistic value of 3.473 (p < 0.05). However, work motivation does not have a significant direct effect on employee performance, as shown by the significance value of 0.166 (> 0.05). Nonetheless, work motivation has an indirect influence on performance through employee satisfaction as a mediating variable, as evidenced by the path coefficient value, which indicates a full mediation effect. These findings provide recommendations for the management of Al-Qur’an Nurul Falah Islamic Boarding School to formulate policies that enhance work motivation and employee satisfaction in order to improve performance. Moreover, this study contributes theoretically to the development of human resource management studies, particularly within the context of Islamic-based educational institutions.